ANALISIS PENDAPATAN USAHATANI PADI SAWAH PENERIMA BANTUAN DAN BUKAN PENERIMA BANTUAN PEMERINTAH DI DESA PASSO KECAMATAN KAKAS BARAT KABUPATEN MINAHASA - Agustinus Kaliele; Ribka M. Kumaat; Olly E.H. Laoh; Eyverson Ruauw (COCOS, 2014)
ABSRACTAgustinus Kaliele. The Income Analysist of the Government Subsidary Rice Farmingand Non-Subsidary Rice Farming in Passo Village Kakas Barat Subdistrict MinahasaRegency. Under guidance of Ribka M. Kumaat as chairman, with Esry H. Laoh and E.Ruauw as members.The objective of this research is to calculate the des race farming income,bothsubsidy raice farming,and to calculate the difference of income, between them.Samplingmethod used in this research is simple by random sampling. This research used primary andsecondary date. Primary date were obtained from interviewet with raice farmer waithquestioner to collect data. Secondary data were obtained from villagegovernment/administration office. The data analysis was qualitative, presented in narrativedescriptive from.This research shows that in average subsidier farmer’s income is more than nonsubsidaryfarmer’s income. Subsidary farmer’s rate income is Rp. 11.510.594,4, otherwisenon-subsidier farmer’s rate income is Rp. 8.191.950,4. R/ C analysis done in this researchshowed that R/C ratio for subsidary farmer’s is 3,012, while R/C ratio for non-subsidaryfarmer’s is 2,543. This different income rate caused by subsidary farmer’s got insentive forsupply fertilizer and pesticide, so that the used of it can raised the productivity and income ofsubsidary farmers.